Heaven below here and now! The Zionist Churches in Southern Africa - Grundmann, C. H. (International journal for the Study of the Christian Church, 2006)
With their emphasis on healing, Zionist churches in southern Africa currently represent by far the largest group among the so-called African Independent or Indigenous Churches (AICs) and, as such, a type of church in their own right. They reflect, in short, an indigenous response to the challenges of modernity, as experienced in their respective socio-political, religious, and cultural settings. After sketching the history of their origin, which is linked to J. A. Dowie as well as to the Keswick movement, and describing the worship and congregational life ‘in Zion' in some detail, the article concludes with a theological reflection about the lived ecclesiology and pneumatology of these churches, which deeply challenge the very perception of established Christian theologies. The aim is to stimulate serious dialogue, which, as the author is convinced, will lead to an authentic re-owning of the Christian tradition by all the Church. © 2006 Taylor & Francis Group, LLC.
paid